Cytokines and Chemokines as Biomarkers of Community-Acquired Bacterial Infection - Michal Holub; David A. Lawrence; Nancy Andersen; Alžběta Davidová; Ondřej Beran; Vilma Marešová; Pavel Chalupa (Mediators of Inflammation)
Routinely used biomarkers of bacterial etiology of infection, such as C-reactive protein and procalcitonin, have limited usefulness for evaluation of infections since their expression is enhanced by a number of different conditions. Therefore, several inflammatory cytokines and chemokines were analyzed with sera from patients hospitalized for moderate bacterial and viral infectious diseases. In total, 57 subjects were enrolled: 21 patients with community-acquired bacterial infections, 26 patients with viral infections, and 10 healthy subjects (control cohorts). The laboratory analyses were performed using Luminex technology, and the following molecules were examined: IL-1Ra, IL-2, IL-4, IL-6, IL-8, TNF-α, INF-γ, MIP-1β, and MCP-1. Bacterial etiology of infection was associated with significantly (P<0.001) elevated serum concentrations of IL-1Ra, IL-2, IL-6, and TNF-α in comparison to levels observed in the sera of patients with viral infections. In the patients with bacterial infections, IL-1Ra and IL-8 demonstrated positive correlation with C-reactive protein, whereas, IL-1Ra, TNF-α, and MCP-1 correlated with procalcitonin. Furthermore, elevated levels of IL-1Ra, IL-6, and TNF-α decreased within 3 days of antibiotic therapy to levels observed in control subjects. The results show IL-1Ra as a potential useful biomarker of community-acquired bacterial infection.